Multicultural Group Counseling Based on Malay Cultural Values "Saprahan" in Cultivating Attitudes of Tolerance in Adolescents (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
The existence of various youth conflicts carried out in groups has an impact on other members to be carried away by negative thought patterns that cause a lack of tolerance for mutual respect and acceptance of others. To create harmony, group counseling is needed to overcome multicultural problems and ensure that each member must feel heard and understand a problem that occurs so that it is hoped that they will realize the importance of mutual respect in every cultural difference. This study aims to be able to determine efforts to instill an attitude of tolerance through multicultural group counseling based on Saprahan Malay cultural values and the implementation of group counseling based on Saprahan Malay traditional cultural values to create an attitude of respecting differences, accepting others, and of course having an attitude of tolerance. The research method used is a literature review study, which involves analysis of various literature, including journals, articles, and relevant documents that discuss Saprahan Malay cultural values, multicultural group counseling, and tolerance. The results of the study show that group counseling based on Saprahan Malay traditional cultural values is able to teach members to understand equality through ways of interacting, being harmonious, establishing intimacy, and being civilized, as well as building togetherness in humanity without looking at levels of status and cultural differences